In vitro evaluation of microleakage around orthodontic brackets using laser etching and Acid etching methods. - Mohammad Hossein Toodehzaeim; Sogra Yassaei; Maryam Karandish; Sedigeh Farzaneh (Tehran University of Medical Sciences, 2014)
path of microleakage between the enamel and adhesive potentially allows microbial ingress that may consequently cause enamel decalcification. The aim of this study was to compare microleakage of brackets bonded either by laser or acid etching techniques.The specimens were 33 extracted premolars that were divided into three groups as the acid etching group (group 1), laser etching with Er:YAG at 100 mJ and 15 Hz for 15s (group 2), and laser etching with Er:YAG at 140 mJ and 15 Hz for 15s (group 3). After photo polymerization, the teeth were subjected to 500 thermal cycles. Then the specimens were sealed with nail varnish, stained with 2% methylen blue for 24hs, sectioned, and examined under a stereomicroscope. They were scored for marginal microleakage that occurred between the adhesive-enamel and bracket-adhesive interfaces from the occlusal and gingival margins. Data were analyzed with the Kruskal- Wallis test.For the adhesive-enamel and bracket-adhesive surfaces, significant differences were not observed between the three groups.According to this study, the Er:YAG laser with 1.5 and 2.1 watt settings may be used as an adjunctive for preparing the surface for orthodontic bracket bonding.